Transungual Drug Delivery: An Overview - Vivek B. Rajendra, Anjana Baro, Abha Kumari, Dinesh L. Dhamecha, Swaroop R. Lahoti, Santosh D. Shelke (Journal of Applied Pharmaceutical Science)
The body normally hosts a variety of microorganisms, including bacteria and fungi. Some of these are useful to the body and others may cause infections. Fungi can live on the dead tissues of the hairs, nails. Continuous exposal of nail to warm, moist environments usually develops nail infection. Nail plate is main route for penetration of drug. Varity of conventional formulation like gel, cream and also oral antifungal are available for treatment of nail infection. The nail lacquer is a new drug delivery system in treatment of nail infections. The major hurdle associated with developing nail lacquers treatment for nail disorders is to deliver the active (antifungal) therapeutically effective concentrations to the site of infection, which is often under nail. However possible means to enhance nail penetration must be explored in greater depth before effective local treatments for fungal nail infections are developed. Lack of proper in vitro methods to measure the extent of drug permeation across the nail plate is the major difficulty in the development of transungual delivery. Penetration of topical antifungal through the nail plate requires a vehicle that is specifically formulated for transungual delivery. Recent focus is emphasizing on development of a promising antifungal treatment in form of nail lacquer owing to its beneficial advantages.
Keywords: Nail, Transungual delivery, Nail plate.